Pandemic and Sociosanitary Policies in Latin America - Nercesian, Inés (2021)
This paper analyzes the health and socio-economic policies adopted by six Latin American countries during the SARS-CoV-2’s pandemic: Argentina, Brazil, Chile, Colombia, Mexico, and Peru. It proposes the hypothesis that the behavior of the pandemic and the decisions taken depended on the relationship between relevant situational factors – namely, the profile of the government and state elites – and structural elements such as state capacities, sociodemographic characteristics, and human development indexes. This article adopts a comparative analytic strategy and employs a combination of quantitative and qualitative methodologies.